Nuclear magnetic resonance studies of forearm muscle in Duchenne dystrophy. Issue 6322 (10th April 1982) - Newman, R J; Bore, P J; Chan, L; Gadian, D G; Styles, P; Taylor, D; Radda, G K
Abstract : The forearms of six patients with Duchenne dystrophy were examined by the painless and non-invasive technique of high-resolution nuclear magnetic resonance spectroscopy. The phosphorus spectrum was abnormal in that the ratios of phosphocreatine to adenosine triphosphate and to inorganic phosphate were reduced. Absolute quantification under the conditions of this experiment was not possible but it was probable that in dystrophy the concentration of phosphocreatine in muscle was appreciably reduced. A signal in the phosphodiester region of the spectrum was recorded consistently in patients with dystrophy but not in controls. The intracellular pH of the muscle in the dystrophic patients was abnormally alkaline. The clinical application of nuclear magnetic resonance spectroscopy remains to be proved, but it appears to be a promising non-invasive technique for investigating biochemical abnormalities of muscle disease.